Image Analysis Approach to Understand the Differences in Flour Particle Surface and Shape Characteristics. Issue 3 (11th November 2015) - Siliveru, Kaliramesh; Kwek, Jin W.; Lau, Grace M. L.; Ambrose, R. P. Kingsly
Abstract : The separation efficiency of wheat flour particles based on size, with minimum bran contamination, is important for a flour mill. Separation of flour during fractionation depends on the surface characteristics and shape of flour particles. Wheat flour particle characteristics such as surface lipid content, roughness, and morphology with respect to particle size were studied to better understand the differences between hard and soft wheat flours. Fractal analysis using image analysis was used to ascertain surface roughness. That was in turn verified by atomic force microscopy measurements. Soft wheat flours (soft red winter and soft white) had a higher degree of surface roughness than the hard wheat flours (hard red spring, hard red winter, and hard white). The fractal dimension values ranged from 2.67 to 2.78 and from 2.28 to 2.55 for soft and hard wheat flours, respectively. The surface lipid content increased with particle size in hard wheat but decreased in soft wheat flours. The surface lipid levels ranged from 1.02 to 1.18 and from 2.55 to 2.58% (% of total area) for 45 μm particles in hard wheat flours (hard red spring, hard red winter, and hard white) and soft wheat flours (soft red winter and soft white), respectively. For the 90 μm particles the lipid levels ranged from 1.54 to 1.62 and from 1.70 to 1.83% (% of total area) for flour particles in hard wheat flours (hard red spring, hard red winter, and hard white) and soft wheat flours (soft red winter and soft white), respectively. Surface lipid content and roughness values showed that soft wheat flours will be more cohesive than hard wheat flours. The morphology values revealed the irregularity in flour particles, irrespective of wheat class and particle size, owing to nonuniform fragmentation of protein and starch matrix of the wheat endosperm.